Effect of external pH on ethanol oxidation by Candida utilis - Páca, J; Votruba, J (Folia microbiologica, 1991)
The external pH affects both ethanol and oxygen uptake rates by nongrowing cells of Candida utilis suspended either in distilled water or in phthalate buffer. The buffering properties of organic acids control the maximum rates of exogenous respiration and ethanol uptake. The substrate limitation of ethanol uptake rate and endogenous respiration rate increase proportionally with increasing hydrogen ion concentration in the medium.
Keywords: Oxidation-Reduction; oxidace-redukce; Kinetics; spotřeba kyslíku; ethanol; Ethanol; koncentrace vodíkových iontů; kinetika; Oxygen Consumption; Hydrogen-Ion Concentration; Candida